Pelatihan komputer akuntansi bagi guru-guru SMK - Hajrah Hamzah; Sahade Sahade (DEDIKASI, 2020)
The Community Partnership Program (PKM) program is Barru State Vocational School Teachers. The problem is: (1) the lack of knowledge about the field of accounting science that requires technology, (2) lack of skills to make an application-based accounting cycle (computer accounting) and, (3) the teachers in Barru Vocational High Schools in their activation are still complex and have not been revised into the actual accounting records. The external target is the process of recording and inputting accounting data (accounting cycles) based on the application's financial statements. The method used is: lectures, demonstrations, discussions, questions and answers, and counterpart partners. The agreed results are (1) partners who have knowledge in the field of accounting knowledge that supports technology, (2) partners who have the skills to create application-based accounting cycles and, (3) partners who have the ability to increase knowledge, create, create, financial, efficient and effective